CONUT: A Useful Alarm of Malnutrition in the Centralized Laboratory of a Spanish Hospital - Miriam Menacho-Román; Gilberto Pérez-López; José Manuel del Rey-Sánchez; Domingo Ly-Pen; Antonio Becerra-Fernández (Baqiyatallah University of Medical Sciences, 2018)
Background: Hospital malnutrition, usually secondary to various diseases and their treatments, is an important problem in our clinical practice. For its proper assessment, it is crucial to use a nutritional alert system, such as the CONUT (COntrol NUTrition) program; this tool uses 3 analytical parameters: serum albumin, total cholesterol, and total lymphocyte count. Objective: The current study assessed the results of the implementation of this program in the University Hospital Ramón y Cajal. Methods: The CONUT program has been used in the University Hospital Ramón y Cajal since 2013. This retrospective study, throughout 2016, was conducted in the Central Laboratory of Chemical Biochemistry at the University Hospital Ramón y Cajal. All blood tests with serum albumin, total cholesterol, and total lymphocyte count were studied. The degree of malnutrition was assessed using the scale of normal (=0), mild (=4), moderate (=8), and severe (=12). Results: In 2016, there were 405406 analytics performed in the laboratory of University Hospital Ramón y Cajal. The CONUT tool was applied to 3.64% of them (14741 analytics). In the outpatient setting, the highest malnutrition index comprised patients from the liver transplant consultation department, followed by the cardiology, rheumatology, and oncology departments. With inpatients, the hematology, cardiology, and endocrinology departments showed the most severe malnutrition index. Conclusion: The CONUT system seemed to provide useful information about the cohort of the studied hospital. The results showed that 94% of the patients were not classified with malnutrition, there was no gender predilection, and they were younger than the rest. Patients with more severe malnutrition were usually older and male.